T1 Mapping in Cardiac MRI: Principles, Techniques, and Reference Values of Native Myocardial T1 and Extracellular Volume in Healthy Subjects - Raad, Tammo; Morkovkina, Hanna Ye.; Sydorova, Alyona V.; Tsasiuk, Yevhen Ye.; Yalynska, Tetyana A. (Ukrainian Journal of Cardiovascular Surgery, 2025)
Background. Cardiovascular diseases remain the leading cause of morbidity and mortality worldwide. One of the key aspects of modern cardiac diagnostics is tissue characterization of the myocardium, which enables the identification of early and diffuse changes not detectable by conventional imaging modalities. T1 mapping by cardiac magnetic resonance (MRI) has emerged as a powerful quantitative technique for detecting and monitoring myocardial fibrosis, both focal and diffuse, in a non-invasive and reproducible manner. Aim. The aim of this study was to establish reference values for native T1 and extracellular volume fraction (ECV) of the myocardium using 1.5T MRI in a healthy Ukrainian population, including both pediatric and adult patients, and to evaluate age-related changes in these parameters. Materials and Methods. This prospective study included 312 participants (143 children and 169 adults) who underwent cardiac MRI between 2022 and 2024. All participants had normal echocardiographic findings and no history of cardiovascular or systemic diseases. Cardiac MRI was performed using a 1.5 Tesla scanner (Magnetom Avanto Fit, Siemens Healthineers) with a standardized protocol. Native T1 mapping was performed using a MOLLI sequence before contrast administration, and post-contrast T1 mapping was used to calculate ECV using hematocrit-adjusted formulae. T1 values were measured in the interventricular septum in short-axis slices. Data were stratified into pediatric subgroups: infants (0-1 years), early childhood (2-6 years), school-age children (7-12 years), and adolescents (12-18 years). Adults were further stratified by age: <50 years and ≥50 years. Statistical analyses included ANOVA, t-tests, and Pearson correlation. Results. Native T1 time demonstrated a statistically significant age-dependent increase in pediatric patients. Mean values were: 940±20 ms (0-1 year), 960±20 ms (2-6 years), 980±20 ms (7-12 years), and 1000±20 ms (12-18 years). Adults exhibited stable T1 values with a mean of 1000.2 ms, showing no significant correlation with age (p = 0.501) or sex (p = 0.848). T1 values in adolescents did not differ significantly from adults (p = 0.183), suggesting myocardial tissue maturation by the age of 12-18 years. Comparison between myocardial segments revealed that the interventricular septum had significantly higher T1 values than the lateral wall (p<0.001), supporting previous recommendations to prefer septal measurements for reproducibility. ECV values were calculated in 94 children and 134 adults. The mean ECV in adults was 24.9 % ±1.53, while in children it was 25.0 % ±1.72. Both groups had identical medians (25 %), though children exhibited a broader distribution (22–28 %) compared to adults (24–26 %). No statistically significant differences in ECV were found between age groups (p>0.05). Conclusions. Our findings establish age-specific reference ranges for native T1 and ECV in a healthy Ukrainian cohort using 1.5T cardiac MRI. T1 values increase during childhood and plateau during adolescence, with no further age-related variation in adulthood. ECV remains consistent across age groups but exhibits wider variability in children. These normative values may support improved tissue characterization and diagnostic accuracy for pediatric and adult cardiac conditions. T1 mapping, with its ability to detect early diffuse fibrosis, holds promise as a clinical and research tool in longitudinal cardiac health assessment.